(untitled) (European Journal of Health Research, 2021)
Urinary tract infection is the most frequent non-respiratory bacterial infection in pediatrics. The aim of this study was to determine the presence of antibiotic activity in urine samples and to evaluate its possible influence on the clinical management of pediatric patients. One hundred and thirty-eight patients with clinical suspicion of urinary tract infection were included. There was previous use of antibiotics in 30 urine samples, but only in 18 of these samples antibiotic activity was found by bioassay. This study shows a high percentage of pediatric patients with antibiotic use prior to urine collection. Biochemical parameters of the urine, such as the presence of more than 25 leukocytes per field or positive nitrites, should alert us to the possibility of bacterial infection. The evaluation of the antibiotic activity in the urine of pediatric patients in parallel with microbiological culture and biochemical parameters allows the optimization of the antibiotic treatment.